Humic Substances Alter Ammonia Production and the Microbial Populations Within a RUSITEC Fed a Mixed Hay – Concentrate Diet - Terry, Stephanie A.; Ramos, Aline F. O.; Holman, Devin B.; McAllister, Tim A.; Breves, Gerhard; Chaves, Alexandre V. (Frontiers in Microbiology, 2018)
Humic substances are a novel feed additive which may have the potential to mitigate enteric methane (CH4) production from ruminants as well as enhance microbial activity in the rumen. The aim of this study was to examine the effects of humic substances on fermentation characteristics and microbial communities using the rumen stimulation technique (RUSITEC). The experiment was conducted as a completely randomized design with 3 treatments duplicated in 2 runs (a 15-day period each run) with 2 replicates per run. Treatments consisted of a control diet (forage:concentrate; 60:40) without humic substances or humic substances added at either 1.5 g/d or 3.0 g/d. Dry matter disappearance, pH, fermentation parameters and gas production were measured from d 8 to 15. Samples for microbial profiling were taken on d 5, 10 and 15 using the digested feed bags for solid- associated microbes (SAM) and fermenter fluid for liquid- associated microbes (LAM). The inclusion of humic substances had no effect (P ≥ 0.19) on DM disappearance, pH or the concentrations of VFA. The production of NH3 was linearly decreased (P = 0.04) with increasing levels of humic substances in the diet. There was no effect (P ≥ 0.43) of humic substances on total gas, CO2 or CH4 production. The number of OTUs was significantly reduced in the 3.0 g/d treatment compared to the control on d 10 and 15; however, the microbial community structure was largely unaffected (P > 0.05). In the SAM samples, the genera Lachnospiraceae XPB1014 group, Succiniclasticum, and Fibrobacter were reduced in the 3.0 g/d treatment and Anaeroplasma, Olsenella, and Pseudobutyrivibrio were increased on d 5, 10 and 15. Within the LAM samples, Christensenellaceae R-7 and Succiniclasticum were the most differentially abundant genera between the control and 3.0 g/d HS treatment samples (P < 0.05). This study highlights the potential use of humic substances as a natural feed additive which may play a role in nitrogen metabolism without negatively affecting the ruminal microbiota.